2018
DOI: 10.1103/physrevapplied.10.024016
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic Insight into the Formation of Metal-Graphene One-Dimensional Contacts

Abstract: Motivated by the need to control the resistance of metal-graphene interfaces, we have simulated the structural and transport properties of edge contacts upon their formation. Our first-principles calculations reveal that the contacts evolve in a nontrivial way depending on the type of metal and the chemical contamination of the graphene edge. In particular, our results indicate that the origin of the low experimental resistance of chromium-graphene edge contacts is related to their weaker variation upon contam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…[4][5][6][7][8][9][10][11][12] Quantum-chemical details are often critical for describing local electronic structure, chemical contacts (e.g. electrodes [13,14]) and electrostatics in realistic nano-electronic devices. This is especially clear in a context of one-atom-thick twodimensional (2D) devices, [7,15,16] where details on the atomic scale govern the electronic behavior.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12] Quantum-chemical details are often critical for describing local electronic structure, chemical contacts (e.g. electrodes [13,14]) and electrostatics in realistic nano-electronic devices. This is especially clear in a context of one-atom-thick twodimensional (2D) devices, [7,15,16] where details on the atomic scale govern the electronic behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the graphene edge is in direct contact with the Ni and forms an ohmic contact. 19,24,25 At this point, graphene still covers the entire chip apart from directly below both metal contacts. The remaining graphene has been patterned into 6 µm long and 50 µm wide channels, before 100 nm thick aluminum (Al) has been deposited as antennas, transmission lines and contact pads.…”
Section: Ure 1amentioning
confidence: 99%
“…The nonequilibrium Green's function (NEGF) is often used to describe the structure-dependent charge transport [23]. Many works using NEGF combined with Landauer formula for conductance are conducted to study the transport across molecular junctions [24][25][26][27], nanotransistors [28,29], grain boundaries in two-dimensional materials [30], metal-semiconductor interfaces [31,32], metalmetal interfaces in magnetic multilayers [33][34][35][36] and semiconductor interfaces [37,38]. In particular, Bellotti et al investigated the carrier transport through semiconductor interfaces in the presence of positional and compositional disorders using NEGF and found that the disorder significantly impeded the coherent propagation of carriers through mul- tiple interfaces [37].…”
Section: Introductionmentioning
confidence: 99%